Examining challenges to reliability of health service accreditation during a period of healthcare reform in Australia. Issue 7 (16th November 2015) - Greenfield, David; Debono, Deborah; Hogden, Anne; Hinchcliff, Reece; Mumford, Virginia; Pawsey, Marjorie; Westbrook, Johanna; Braithwaite, Jeffrey
Abstract : Purpose: – Health systems are changing at variable rates. Periods of significant change can create new challenges or amplify existing barriers to accreditation program credibility and reliability. The purpose of this paper is to examine, during the transition to a new Australian accreditation scheme and standards, challenges to health service accreditation survey reliability, the salience of the issues and strategies to manage threats to survey reliability. Design/methodology/approach: – Across 2013-2014, a two-phase, multi-method study was conducted, involving five research activities (two questionnaire surveys and three group discussions). This paper reports data from the transcribed group discussions involving 100 participants, which was subject to content and thematic analysis. Participants were accreditation survey coordinators employed by the Australian Council on Healthcare Standards. Findings: – Six significant issues influencing survey reliability were reported: accreditation program governance and philosophy; accrediting agency management of the accreditation process, including the program's framework; survey coordinators; survey team dynamics; individual surveyors; and healthcare organizations' approach to accreditation. A change in governance arrangements promoted reliability with an independent authority and a new set of standards, endorsed by Federal and State governments. However, potential reliability threats were introduced by having multiple accrediting agencies approved to survey against the new national standards. Challenges that existed prior to the reformed system remain. Originality/value: – Capturing lessons and challenges from healthcare reforms is necessary if improvements are to be realized. The study provides practical and theoretical strategies to promote reliability in accreditation programs.